Examination of Field Electron Emission from Knife-Edge Structures - Sule, Nishant (My University, 2009)
This thesis reports the experimental and modeling research carried out on eld and thermal emission from knife-edge structures. Field emission arises from electron emission from a surface under the in uence of intense electric elds by the process of quantum mechanical tunneling through the potential barrier at the material-vacuum interface. The eld emission experiments were done on the Madison Cathode Experiment (MACX) setup with cathodes fabricated with raised vanes or knife-edges. Measurements of emission current as a function of applied voltage, anode-cathode spacing and temperature were recorded using an ampli er developed for these experiments and analysis of the experimental data was done using Fowler-Nordheim theory as well as thermal- eld emission processes. Cathode parameters such as work function ( ), eld enhancement factor ( ) and the e ective emitting area (A) are extracted for the copper knife edge (CKE) cathodes making use of thermal and eld emission data. The ranges of cathode parameters thus obtained are, 2.96{4.7 eV, 400{440 and A 6.3{6.66 10 7 m2. Evidence of space charge limited emission current is also obtained for these CKE cathodes. Investigations of eld emission from lanthanum hexaboride (LaB6) thin lms ( 300 nm) sputter deposited on these CKE cathodes with a titanium adhesion layer on copper are also reported. These thin lms of LaB6 have a low work function ( 2:6 eV) and are expected to enhance the emission current density from the CKE cathodes. However, the experiments obtain a lower emission current density than bare copper and nonlinear eld emission current variations from these LaB6 lms at elevated temperatures ( 200deg). A hypothesis based on electron transport in the copper metal and the LaB6 thin lm is presented to explain these observations. In conclusion, some future experiments are suggested to further investigate eld emission from CKE cathodes as well as eld emission properties with di ering LaB6 thickness thin lms on CKE structures.